Body weight and sensitivity of screening mammography. (June 2016) - Njor, Sisse H.; von Euler-Chelpin, My; Tjønneland, Anne; Vejborg, Ilse; Lynge, Elsebeth
Abstract: Aim: Obese women tend to participate less in breast cancer screening than normal weight women. However, obese women have fattier breast than normal weight women, and screening mammography works better in fatty than in dense breasts. One might, therefore, hypothesise that obese women would actually benefit more from screening than other women. Methods: We combined data from the Danish Diet, Cancer and Health study and the organised population-based screening mammography programme in Copenhagen, Denmark. Women were categorised according to body mass index (BMI) (<20; 20 to <25; 25 to <30; 30 to <35, and 35+). We measured recall rate, sensitivity and specificity for subsequent screens with a 2-year follow-up period. Results: The study included 6787 women. The recall rate varied from 1.4% for women with BMI <20 to 1.9% for women with BMI 35+, test for trend p = 0.86. Sensitivity varied from 42% (95% confidence interval [CI] 20–64%) for women with BMI <20 to 100% (95% CI 69–100%) for women with BMI 35+, test for trend p = 0.015. Specificity was fairly constant across BMI levels, being on average 98.8%, test for trend p = 0.79. Conclusion: This study showed that obese women were the ones with the highest sensitivity of screening mammography, while the specificity of screening remained stable across weight groups. Screening programmes should be organized to encourage these women to overcome obstacles for participation. Highlights: Our study shows that the sensitivity of screening mammography increases with increasing body mass index (BMI). The specificity of screening mammography remains constant with increasing BMI. Information material should encourage women with a high BMI to participate in screening.